What does a social justice lawyer need to know?. (June 2022) - Rice, Simon
Social justice lawyers work to address social phenomena such as inequality, disadvantage, discrimination, marginalisation, oppression and abuse, addressing the immediate needs of a client, or the structural causes of those needs, or both. But social justice lawyers are rarely explicit about the specific knowledge and qualities that their lawyering demands, and that they demonstrate. Across doctrine, theory, values, skills and ethics, there is benefit in setting out what it can mean to be a social justice lawyer, for discussion, comment, criticism, reflection and refinement.